Sustained Hemodynamic and Clinical Improvements for a Patient With Idiopathic Pulmonary Arterial Hypertension Over 1.5 Years After Balloon Atrial Septostomy: A Case Report - Liang, Kae-Woei; Wang, Kuo-Yang (Frontiers in Cardiovascular Medicine, 2022)
Balloon atrial septostomy (BAS) is an indicated treatment for subjects with idiopathic pulmonary arterial hypertension (IPAH), particularly for those with advanced right heart failure before bridging to lung transplantation. The mid-term clinical and hemodynamic benefits of BAS are not well studied. Here, we present a young IPAH female patient who had received maximal target medication and was admitted to our hospital due to advanced right heart failure. She had transition of subcutaneous to intravenous (IV) prostacyclin analogues (PA) injection and was registered for lung transplantation. The baseline mean right atrium (RA) pressure was 14 mmHg. BAS was performed with a balloon of 6 mm under intracardiac echocardiography (ICE) guidance. Systemic cardiac output (CO) (2.9 to 3.5 L/min) and oxygen delivery (OD)(291 to 318 ml/min) both increased after the BAS. Right heart failure was alleviated to function class II. One and a half years later, she received cardiac catheterization again. The second baseline mean RA pressure was 5 mmHg, left atrium (LA) pressure was 2 mmHg and systemic CO was 3.3 L/min. These data indicated sustained hemodynamic improvements. The second course of BAS was performed under ICE guidance with a balloon of 8 mm. After the second BAS, her RA pressure was 3 mmHg, LA pressure was 3 mmHg and CO was 3.4 L/min. In conclusion, BAS and IV PA infusion were effective in maintaining mid-term hemodynamic benefits and in stabilizing the critical right heart failure in an IPAH patient over a 1.5-year period. Keywords: balloon atrial septostomy (BAS); case report; idiopathic pulmonary arterial hypertension (IPAH); intracardiac echocardiography (ICE); prostacyclin analogues